Studi Komparatif Sistem Sambungan Beton Pracetak Wet Joint dan Dry Joint terhadap Fleksibilitas Desain Arsitektur pada Bangunan - Harmaezza Harmaezza; Indri Rahma Puspadila; Sania Rahmi Apriliani (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The development of precast concrete systems has positioned connection systems as critical elements that influence not only structural performance but also architectural design flexibility. This study aims to comparatively examine dry joint and wet joint precast concrete connection systems in relation to architectural design flexibility and their implications for architects’ design freedom. A qualitative approach using descriptive comparative methods was employed, combining literature review and analysis of selected precast concrete building case studies utilizing both connection systems. The analysis focuses on architectural flexibility, including spatial reconfiguration, mass development, and future building expansion potential. The results indicate that dry joint systems primarily support flexibility at the spatial and modular scale, allowing layout changes and functional adaptation with minimal structural intervention, while limiting mass articulation and vertical development. In contrast, wet joint systems provide flexibility at the building scale through higher structural continuity and reliability, enabling complex forms, large spans, and high-rise development, but offering limited flexibility for spatial modification after construction. This study highlights that the selection of precast concrete connection systems constitutes a strategic architectural decision that shapes the direction of design flexibility throughout the building life cycle.